Measuring the effectiveness of adaptation investments across a project portfolio - Njuguna, Lucy; Rosenstock, Todd (2024)
As climate change adaptation becomes a key focus of programs and projects, donors and fund managers must assess the overall impact of their investments through robust "adaptation tracking" mechanisms. This involves monitoring, evaluating, and communicating progress but is hindered by challenges such as defining adaptation success, selecting suitable indicators, and attributing outcomes to specific investments. Additional obstacles include data limitations, resource and capacity constraints, integration with existing systems, and ensuring equity and inclusivity. The dynamic nature of climate risks and the complexity of aggregating diverse, context-specific data across portfolios further complicate systematic evaluation efforts. This working paper outlines key recommendations for the design of portfolio-level tracing systems, based on a review of selected funds and organizations.